MDA-MB-231 cell apoptosis in vitro induced by dihydromyricetin - ZHOU Fang-zhen; ZHANG Xiao-yuan; SUN Fen-yong; GUO Yong (浙江大学学报. 农业与生命科学版)
To investigate the effect of dihydromyricetin (DMY) induction on MDA-MB-231 cell apoptosis and its mechanism, the changes of cell morphological characteristics were observed under inverted microscope. Apoptosis, intracellular Ca2+ level and the mitochondrial innermembrane potential (ΔΨm) were analyzed by flow cytometry (FCM). Western blotting was employed to detect the expression of caspase-3 and caspase-9. The results showed that the cell size and volume became smaller with increasing concentration of DMY. Increased Sub-G1 peak and intracellular Ca2+ level, as well as the decreased mitochondrial ΔΨmin MDA-MB-231 cells were obviously observed in a dose-dependent manner. Western blotting analysis showed that DMY dose-dependently increased the expression of caspase-3 and caspase-9 in MDA-MB-231 cells. These results indicate that DMY can induce MDA-MB-231 cell apoptosis by the mitochondrial pathway.